The HIV-2 OGH double reporter virus shows that HIV-2 is less cytotoxic and less sensitive to reactivation from latency than HIV-1 in cell culture - Anne Bruggemans; Gerlinde Vansant; Paulien Van de Velde; Zeger Debyser (Elsevier, 2023)
A better understanding of HIV-1 latency is a research priority in HIV cure research. Conversely, little is known about the latency characteristics of HIV-2, the closely related human lentivirus. Though both viruses cause AIDS, HIV-2 infection progresses more slowly with significantly lower viral loads, even when corrected for CD4+ T cell counts. Hence a direct comparison of latency characteristics between HIV-1 and HIV-2 could provide important clues towards a functional cure.Transduction of SupT1 cells with single-round HIV-1 and HIV-2 viruses with an enhanced green fluorescent protein (eGFP) reporter showed higher levels of eGFP expression for HIV-2 than HIV-1, while HIV-1 expression appeared more cytotoxic. To compare HIV-1 and HIV-2 gene expression, latency and reactivation in more detail, we have generated HIV-2 OGH, a replication deficient, near full- length, double reporter virus that discriminates latently and productively infected cells in cell culture. This construct is based on HIV-1 OGH, and to our knowledge, first of its kind for HIV-2. Using this construct we have observed a higher eGFP expression for HIV-2, but higher losses of HIV-1 transduced cells in SupT1 and Jurkat cells and a reduced sensitivity of HIV-2 for reactivation with TNF-α. In addition, we have analysed HIV-2 integration sites and their epigenetic environment. HIV-1 and HIV-2 share a preference for actively transcribed genes in gene-dense regions and favor active chromatin marks while disfavoring methylation markers associated with heterochromatin. In conclusion the HIV-2 OGH construct provides an interesting tool for studying HIV-2 expression, latency and reactivation. As simian immunodeficiency virus (SIV) and HIV-2 have been proposed to model a functional HIV cure, a better understanding of the mechanisms governing HIV-2 and SIV latency will be important to move forward. Further research is needed to investigate if HIV-2 uses similar mechanisms as HIV-1 to achieve its integration site selectivity.